2022
DOI: 10.1002/micr.30978
|View full text |Cite
|
Sign up to set email alerts
|

Free tissue reconstruction in the “vessel‐depleted” neck: A multi‐institutional cohort study

Abstract: Objectives Much of the literature on free tissue reconstruction in the “vessel‐depleted” neck is focused on identification of vessels outside the pretreated field and data on free flap outcomes when infield microvascular anastomosis is performed remain scarce. We aim to report on free flap outcomes and recipient vessel choice in a large cohort of patients with prior radiation and neck dissection (RTND) to the ipsilateral side of vessel anastomosis. Methods A retrospective review was performed including patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In patients who do have adequate vessel options within the treatment field, Chang et al reported that the use of infield microvascular anastomosis in patients who previously received radiation therapy and neck dissection can be done safely with free flap success rate of 94.4% [5 ▪ ]. In this multiinstitution cohort study, the most common recipient arteries included facial followed by external carotid, and superior thyroid.…”
Section: Finding Adequate Vessel Options In a Vessel-depleted Neckmentioning
confidence: 85%
See 1 more Smart Citation
“…In patients who do have adequate vessel options within the treatment field, Chang et al reported that the use of infield microvascular anastomosis in patients who previously received radiation therapy and neck dissection can be done safely with free flap success rate of 94.4% [5 ▪ ]. In this multiinstitution cohort study, the most common recipient arteries included facial followed by external carotid, and superior thyroid.…”
Section: Finding Adequate Vessel Options In a Vessel-depleted Neckmentioning
confidence: 85%
“…The authors demonstrated that even in heavily treated necks, adequate vessel options may still be available to support microvascular reconstruction. Further, use of these vessels within the treatment field does not lead to a prohibitive decrement in free flap outcomes [5 ▪ ].…”
Section: Finding Adequate Vessel Options In a Vessel-depleted Neckmentioning
confidence: 99%